2014
DOI: 10.5005/jp-journals-10008-1168
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcome of Ahmed Valve Implantation in Mexican Patients with Neovascular Glaucoma

Abstract: Purpose: To describe clinical results of Ahmed glaucoma valve implantation in Mexican patients with neovascular glaucoma (NVG).Materials and methods: We reviewed records of 60 eyes of 60 patients with NVG who underwent Ahmed valve implantation, with a follow-up period of 1 year. We identified successful and failed cases and compared baseline and follow-up characteristics to identify possible differences between both groups.Results: We classified 36 eyes (60%) as successful and 24 (40%) as failed cases. We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Yalvac reported 63.2 and 56.2 % of success rates at 1 and 2 years after Ahmed glaucoma valve implantation, respectively [72]. Hernandez-Oteyza recently reported a success rate of 60 % at 1 year of follow-up and found that a hypertensive phase in the postoperative period and a worse preoperative BCVA to be risk factors for Ahmed valve surgical failure in patients with NVG [73]. Netland et al found that the success rate was significantly lower over time in eyes with NVG compared with controls.…”
Section: Introductionmentioning
confidence: 99%
“…Yalvac reported 63.2 and 56.2 % of success rates at 1 and 2 years after Ahmed glaucoma valve implantation, respectively [72]. Hernandez-Oteyza recently reported a success rate of 60 % at 1 year of follow-up and found that a hypertensive phase in the postoperative period and a worse preoperative BCVA to be risk factors for Ahmed valve surgical failure in patients with NVG [73]. Netland et al found that the success rate was significantly lower over time in eyes with NVG compared with controls.…”
Section: Introductionmentioning
confidence: 99%
“…Yalvac et al [77] reported a success rate of 63.2 and 56.2 % at 1 and 2 years after Ahmedʼs glaucoma valve surgery, respectively. Hernandez-Oteyza et al [78] showed a success rate of 60 % at the 1-year follow-up, indicating that a hypertensive phase in the postoperative period and a lower preoperative BCVA are risk factors for surgical failure in this group of patients [78]. The success rate over time was found to be substantially lower in eyes with NVG compared with controls.…”
Section: Trabeculectomy (Trab)mentioning
confidence: 89%
“…A retrospective analysis of Ahmed GDIs showed that NVG eyes had a significantly lower rate of complete success compared with control eyes without neovascularization at both 1 year (73.3% vs. 89.2%, respectively) and 5 years (20.6% vs. 81.8%, respectively) of follow-up 64 . Similarly, a retrospective review of NVG eyes that underwent Ahmed tube shunts reported an overall success rate of 60.0% at 1 year and found that a postoperative hypertensive phase was correlated with a higher risk of failure 69 . In addition, a prospective study of NVG eyes who underwent placement of a Molteno GDI demonstrated relatively poor rates of IOP control, with success rates of 72.0% at 1 year and 40.0% at 5 years, regardless of the use of adjunctive medications 65 .…”
Section: Surgical Management Of Nvgmentioning
confidence: 96%
“…64 Similarly, a retrospective review of NVG eyes that underwent Ahmed tube shunts reported an overall success rate of 60.0% at 1 year and found that a postoperative hypertensive phase was correlated with a higher risk of failure. 69 In addition, a prospective study of NVG eyes who underwent placement of a Molteno GDI demonstrated relatively poor rates of IOP control, with success rates of 72.0% at 1 year and 40.0% at 5 years, regardless of the use of adjunctive medications. 65 Another retrospective study evaluating the use of Molteno GDIs in NVG eyes found similar success rates of 62.1% at 1 year, 43.1% at 3 years, and 10.3% at 5 years of follow-up.…”
Section: Glaucoma Drainage Implants (Gdis)mentioning
confidence: 99%